Flight of the quetzalcoatlus - Stone, Rex; Spoor, Mike illustrator (New York : Scholastic, 2008)
Tom and Jamie are on a rescue mission: a quetzalcoatlus has dino-napped their friend the wannanosaurus. With a wingspan of 40 feet, the quetzalcoatlus is a high flier--and a fast one. Tracking Wanna won't be easy, but Tom and Jamie have a plan.
P
b
b
Keywords: Pterodactyls -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Boys -- Juvenile fiction